Telehealth in breast cancer following the coronavirus disease 2019 pandemic - Jean Zeghondy; Elie Rassy; Pietro Lapidari; Roland Eid; Barbara Pistilli (Open Exploration Publishing Inc., 2023)
Breast cancer (BC) is the second most diagnosed cancer in 2018 with around 2.3 million cases globally in 2020. In March 2020 and after its worldwide spread, the World Health Organization (WHO) declared the coronavirus disease 2019 (COVID-19) outbreak, a respiratory disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus, a pandemic. During this time, cancer patients were heavily impacted and their treatment plans were changed due to measures to fight the disease and solutions had to be found to maintain their follow-up and management from a distance. Some cancer groups worldwide have recommended then the use of telemedicine for oncology patients to ensure the continuity of medical care during the pandemic. This method was considered effective and clinicians worldwide continued using telehealth even after the cessation of worldwide restrictions. To this end, current up-to-date data on the use of telemedicine in BC patient after the COVID-19 outbreak are summarized in this narrative review.